Security testing handbook for banking applications - Doraiswamy, Arvind (IT Governance Pub., 2009)
Security Testing Handbook for Banking Applications is a specialised guide to testing a wide range of banking applications. The book is intended as a companion to security professionals, software developers and QA professionals who work with banking applications.